Sistem Informasi Pemesanan Produk Pada Percetakan Seventeen Berbasis Website - Hellena Indriani; Ratih (Jurnal Teknologi dan Bisnis, 2022)
Seventeen Printing is a company engaged in the digital printing sector which is located at Jl. Dr. Wahidin - Sindangsari. The product ordering system still uses manual record filing documentation. Often records are lost or archives are corrupted. This causes the order data is not well documented so that errors often occur in the production department. An information system is needed that can simplify the product ordering process as well as tidy up ordering documentation. The system development method used in this research process is the waterfall method by implementing PHP, CSS, HTML and MySQL databases in building information systems. System testing uses the Blackbox method. The research results obtained are product ordering information systems that can make it easier for customers to make product ordering transactions and make it easier for admins to document transactions so that there are no errors in the production process. Keywords: Information Systems, Product Ordering, Waterfall, PHP, CSS, HTML, MySQL